2015
DOI: 10.1002/ejoc.201500511
|View full text |Cite
|
Sign up to set email alerts
|

Indaphyrins and Indachlorins: Optical and Chiroptical Properties of a Family of Helimeric Porphyrinoids

Abstract: Indaphyrins and indachlorins possess large chiral porphyrinoid π‐systems with particularly long‐wavelength absorption properties. All indaphyrin derivatives, including the indaphyrin MII complexes (M = NiII, CuII, ZnII, and PtII), adopt strongly ruffled conformations incorporating a helimeric twist, thus forming two stereochemically stable helimeric enantiomers. Their degree of ruffling is modulated by the coordination to metal ions or pyrrole ring modifications. Resolution of the racemic mixtures of the helim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 63 publications
1
23
0
Order By: Relevance
“…It is noteworthy that in all cases described by Pecul and Ruud and Crawford et al., RI‐CC2 or EOM‐CCSD calculations always agreed with TD‐DFT on the predicted sign of CPL bands . The present inconsistency between TD‐DFT and coupled‐cluster calculations is, to the best of our knowledge, unprecedented in the context of CPL, whereas in the context of ECD calculations some discrepancies between TD‐DFT and CC2 have been reported, mostly related to transitions with large charge‐transfer character …”
Section: Resultsmentioning
confidence: 54%
“…It is noteworthy that in all cases described by Pecul and Ruud and Crawford et al., RI‐CC2 or EOM‐CCSD calculations always agreed with TD‐DFT on the predicted sign of CPL bands . The present inconsistency between TD‐DFT and coupled‐cluster calculations is, to the best of our knowledge, unprecedented in the context of CPL, whereas in the context of ECD calculations some discrepancies between TD‐DFT and CC2 have been reported, mostly related to transitions with large charge‐transfer character …”
Section: Resultsmentioning
confidence: 54%
“…In a separate contribution we demonstrated that the π‐system of free base and metalated indaphyrins show the hallmarks of a porphyrin‐type π‐system, as expressed in the relative order of the frontier orbitals according to the Gouterman four‐orbital model of porphyrinoid spectra 23. We therefore understand them as porphyrin analogues, irrespective of some chlorin‐like characteristics (see regioselectivity of the dihydroxylation).…”
Section: Resultsmentioning
confidence: 80%
“…The crystal structure of the starting indaphyrin 9 shows that it is ruffled, expressing helimeric chirality (Figures 1 and 3; for a detailed discussion of the conformation of 9 and its derivatives, see below). Assuming this conformation is also maintained in the solution state (a supposition supported by the ability to separate indaphyrin into its enantiomers by chiral HPLC),23 it provides the key to understanding the 1 H NMR signal pattern. The vic ‐ cis ‐diol moiety breaks the two‐fold rotational symmetry of the ruffled macrocycle, rendering all protons diastereotopic (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations